Environmental science a global concern - Cunningham, William P.; Cunningham, Mary Ann (McGraw Hill Education, 2015)
Offers a presentation of environmental science for non-science majors which emphasizes critical thinking, environmental responsibility, and global awareness. This book is intended for use in a one or two-semester course in environmental science, human ecology, or environmental studies at the college or advanced placement high school level.